Shorebird and Passerine Abundance and Habitat Use at a High Arctic Breeding Site: Creswell Bay, Nunavut - Latour, Paul B.; Machtans, Craig S.; Beyersbergen, Gerard W. (ARCTIC, 2010)
Shorebirds and passerines were surveyed at Creswell Bay, Somerset Island, in the High Arctic Ecozone (Canadian Arctic Islands) during the breeding season (June and July, 1995–97) and in August 1995 (post-breeding). The study area, situated on the north and south sides of Creswell Bay, consisted of sedge marsh and sedge wetland in the lowest areas, with shrub tundra dominated by Dryas spp. or Cassiope spp. and sparse herbaceous tundra over more upland areas. Surveys were carried out on 400 x 400 m plots distributed among the vegetation types according to their relative amounts within the study areas (34 plots in 1995; 33 plus 56 new plots in 1997). Eleven shorebird and three passerine species were observed during the surveys. Densities of breeding shorebirds were similar in 1995 and 1997 (37.3 and 33.1 birds/km2), while in 1996 a late spring with heavy snow cover resulted in reduced numbers of birds and no breeding. Shorebirds and passerines were much more numerous in sedge marsh and sedge wetland. White-rumped sandpiper (Calidris fuscicollis) and red phalarope (Phalaropus fulicarius) were the most abundant shorebirds breeding at Creswell Bay, and Lapland longspur (Calcarius lapponicus) was the most abundant breeding passerine. White-rumped sandpiper and sanderling (Calidris alba) were the most numerous species present after the breeding period. American golden-plover (Pluvialis dominica), red phalarope, and white-rumped sandpiper showed significant habitat preferences. An estimated 10 341 (± 6596; 95% CI) shorebirds were on the north area in 1995 and 14 840 (± 10 744) on both areas in 1997. The estimated maximum numbers over both years of white-rumped sandpiper (6769 ± 3725) and buff-breasted sandpiper (Tryngites subruficollis) (908 ± 1169) at Creswell Bay were more than 1% of the species’ estimated national populations (1.5% and 5.1%, respectively). This abundance, along with the relatively high species diversity at this high-latitude site, warrants its continued status as a Canadian Wildlife Service “key ...